Evaluation of a Hydrotreated Vegetable Oil (HVO) and Effects on Emissions of a Passenger Car Diesel Engine - Dimitriadis, Athanasios; Natsios, Ioannis; Dimaratos, Athanasios; Katsaounis, Dimitrios; Samaras, Zissis; Bezergianni, Stella; Lehto, Kalle (Frontiers in Mechanical Engineering, 2018)
In the coming years, the application of paraffinic biofuels, such as Hydrotreated Vegetable Oils (HVO), in the transportation sector is expected to increase. However, as the composition of HVO is different compared to conventional diesel, the engine optimized for conventional fuel cannot take full advantage of the HVO beneficial properties. Suitable adjustment of a number of engine parameters, if not complete engine re-calibration, will enable the full exploitation of such fuels’ potential for lower exhaust emissions and reduced fuel consumption. In the present work, the emission characteristics of HVO fuel in a light-duty Euro 5 diesel engine have been studied, under steady-state operation, as well as during the New European Driving Cycle (NEDC). The study was expanded to the investigation of exhaust emissions under modified Main Injection Timing (MIT) and EGR rate. The NEXBTL fuel, produced by Neste, was considered in the study and was compared with conventional market diesel. Emissions of nitric oxides (NOx), soot, carbon monoxide (CO), carbon dioxide (CO2) and hydrocarbons (HC) were studied. At default MIT and EGR settings the use of HVO resulted in a significant reduction of all regulated emissions. In addition, it was observed that the adjustment of MIT and EGR can enhance the exploitation of HVO potential for emissions reduction, highlighting the differences with the conventional diesel fuel.